Translation Principles vs. Translator Strategies - Lotfipour-Saedi, Kazem (Meta, 1996)
AbstractHaving subscribed to a definite viewpoint on the nature of language and language use in interpersonal verbal transactions, one can set out to characterize the principles governing the translation process. But due to the highly volatile nature of the "context of situation" as a determining factor in the materialization of the language function, the translator cannot operate rigidly according to a set of principles in dealing with every text-type. He should rather use such principles as solid guidelines to make strategic decisions appropriate for every specific context of situation. This paper will first outline the dimensions of translation equivalence within a discoursal approach to language. It will then speculate on the strategies the translator can employ in relation to specific contextual and co-textual factors.